The Radical In/Visibility of Speciesism and Non-human Animals Intrinsic Rights - Genovese, Danila (Italian Sociological Review, 2025)
Non-human animals eem to be almost invisible within Political science and Sociology. Primarily, they are represented as part of the natural environment, deprived of sentiency, agency, and mostly of intrinsic rights to life. Luckily, there are a few authors who address this epistemological gap in the field, and offer a very much needed conceptual re-elaboration of the relationship between the Human and the Animal. In their provocative collection Aphro-ism authors Aph and Syl Ko offer new theoretical frameworks on race, activism regarding non-human animals, and feminism. They engage in the analysis of the interconnected forms of oppressions between species and, by using a feminist approach, they provide a very much needed deconstruction of Eurocentric narratives of race and species. This paper explores whether the notion of interconnectedness of oppression between ‘sub-humanized’ groups and non-human animals, as elaborated by Aph and Syl Ko, can offer effective theoretical and political instruments for advocating for animal liberation and the enforcement of their moral and legal rights. It questions the extent to which any comparison, analogy and eventually coalescence of the notion of human and animal oppression supports a theory and a practice of shared justice or conversely reiterates narratives of anthropocentrism, without leading to a paradigm shift that proposes non- human animals as intrinsic rights- holders and veganism as an obligation towards them.